ANALYSIS OF THE CRITICAL DISCUSSION OF THEO VAN LEEUWEN'S INCLUSION THEORY IN NEWS MEETING CORRUPTION TAKEN FROM “PIKIRAN RAKYAT DAN TRIBUN JABAR” EDITION JANUARY 2019 - Endri Luki Pauji; Rosi Rosi; Rochmat Tri Sudrajat (JLER (Journal of Language Education Research), 2019)
The purpose of this study is to analyze the use of Leeuwen inclusion theory in the news as for the stages used by researchers are (4M) Reading, Understanding, Marking, and Analyzing. In stage (1) the researcher reads the news in the Pikiran Rakyat newspaper, (2) the researcher understands the discourse that is available in the newspaper (3) the researcher marks the discourse to be analyzed and (4) the researcher analyzes the discourse that has been marked based on Lee's inclusion theory. In this study researchers used a qualitative method of describing the findings of data that researchers had discovered. Based on the results of the study it can be concluded, Leeuwen's inclusioan theory found in four criminal news titles with the theme of "corruption" in the People's Mind Newspaper and January 2019 edition of Tribun Jabar amounted to three of the seven existing theories, namely objectivity, Determination, and assimilation -individualization. So, it can be concluded in writing criminal news with the theme of "corruption" Journalists still hide actors. The concealment of actors by journalists is done by using passive sentences in the headline.